Coexistence of the BRCA1 and KRAS mutations in a patient with salivary gland carcinoma arising in mediastinal mature teratoma. Issue 8 (September 2020) - Zhu, Yue-Ting; Chen, Ye; Li, Yue-Hua; Chen, Ni; Zhang, Hong-Wei; Xu, Li-Ming; Liu, Ji-Yan
Abstract : Teratoma with malignant transformation is a rare type of malignant teratoma. In the present case, we describe a patient with salivary gland carcinoma (SGC) generating in mediastinal mature teratoma. Next-generation sequencing showed BRCA1 and KRAS somatic mutations, which might be associated with malignant transformation of the mediastinal mature teratomas. To our knowledge, the present case is the first report of coexistence of BRCA1 and KRAS mutations in mature cystic teratoma with malignant transformation to SGC. And the tumor showed a good response to chemotherapy with cisplatin and paclitaxel according to the transformed histology.